Behavioral and Histopathological Impairments Caused by Topical Exposure of the Rat Brain to Mild-Impulse Laser-Induced Shock Waves: Impulse Dependency - Jitsu, Motoyuki; Niwa, Katsuki; Suzuki, Go; Obara, Takeyuki; Iwama, Yukiko; Hagisawa, Kohsuke; Takahashi, Yukihiro; Matsushita, Yoshitaro; Takeuchi, Satoru; Nawashiro, Hiroshi; Sato, Shunichi; Kawauchi, Satoko (Frontiers in Neurology, 2021)
Although an enormous number of animal studies on blast-induced traumatic brain injury (bTBI) have been conducted, there still remain many uncertain issues in its neuropathology and mechanisms. This is partially due to the complex and hence difficult experimental environment settings, e.g., to minimize the effects of blast winds (tertiary mechanism) and to separate the effects of brain exposure and torso exposure. Since a laser-induced shock wave (LISW) is free from dynamic pressure and its energy is spatially well confined, the effects of pure shock wave exposure (primary mechanism) solely on the brain can be examined by using an LISW. In this study, we applied a set of four LISWs in the impulse range of 15 - 71 Pa･s to the rat brain through the intact scalp and skull; the interval between each exposure was 5 s. For the rats, we conducted locomotor activity, elevated plus maze and forced swimming tests. Axonal injury in the brain was also examined by histological analysis using Bodian silver staining. Only the rats with exposure at higher impulses of 54 and 71 Pa･s showed significantly lower spontaneous movements at 1 day and 2 days post-exposure by the locomotor activity test, but after 3 days post-exposure, they had recovered. At 7 days post-exposure, however, these rats (54 and 71 Pa･s) showed significantly higher levels of anxiety-related and depression-like behaviors by the elevated plus maze test and forced swimming test, respectively. To the best of the authors’ knowledge, there have been few studies in which a rat model showed both anxiety-related and depression-like behaviors caused by blast or shock wave exposure. At that time point (7 days post-exposure), histological analysis showed significant decreases in axonal density in the cingulum bundle and corpus callosum in impulse-dependent manners; axons in the cingulum bundle were found to be more affected by a shock wave. Correlation analysis showed a statistically significant correlation between the depression like-behavior and axonal density reduction in the cingulum bundle. The results demonstrated the dependence of behavior deficits and axonal injury on the shock wave impulse loaded on the brain.